0062 Enhancing Credibility Of Audiovisual Teaching Resources Through The Use Of A Simulated Clinical Environment For Filming. (1st November 2014) - Littley, Nathan; McKelvie, Karen; Harrison, Neil; Smith, Robert
Abstract : Background/context: The use of audiovisual materials for medical education is not a new concept. Many institutions use this as a primary or supplementary learning resource, typically for practical skills teaching. We created a new set of instructional videos for the teaching of clinical examinations, with a focus on ensuring simulated clinical realism. Simulation is a profoundly useful tool in all aspects of healthcare teaching, and its value is much higher with increased realism. 1 We aimed to replicate this value in video form. Description of topic: Our videos were filmed in the Dow Clinical Simulation Suite at Dundee Medical School, using patient actors and real clinicians. The suite is visually representative of working clinical areas within Ninewells Hospital. Patients were dressed in hospital gowns and props were used to set the scene for a particular patient examination. Recognised specialty-specific clinicians performed the examinations. We aimed to make the videos look as realistic as possible, such that learners would feel confident to replicate the skill in the clinical environment. Improvements/outcomes: When asked to compare between existing skills videos and our new set of videos, learners consistently valued the simulated clinical setting and attention to realism, suggesting that these help particularly when transferring the skill to clinical practice. It makes the skill more relatable and relevant, and aids learning of salient parts of a skill which might otherwise not have been represented in the video. Importance of the use of a simulated clinical environment was rated on average 4.17 out of 5 for transferring the skill to real practice. Take home messages: Video teaching resources for practical skills are increasingly being used. However, their credibility can be improved when they replicate real-life practice as closely as possible. This can be achieved with the use of established technologies and techniques seen in other simulation practices. Reference: Kneebone RL, Kidd J, Nestel D, Barnet A, Lo B, King R, et al . Blurring the boundaries: scenario-based simulation in a clinical setting. Med Educ 2005;39(6):580–7